(untitled) (Bombay Hospital Journal, 2024)
A CASE OF CONTRACTED SOCKET RECONSTRUCTION IN RURAL PART INDIA Abstract / summary: An empty orbit can result in facial disfigurement and thereby have an emotional and psychologic impact on the patient and can lead to an economic setback. Treating the patient with an orbital reconstruction can help the patient to live a normal life and gain acceptance in society. Reconstruction of a severely contracted anophthalmic socket is a challenge for an ophthalmic surgeon as there is shrinkage of orbital tissue with shallow fornices and deep superior sulcus and can give rise to a cosmetic anomaly. In our case we could correct to a maximum extent the cosmetic defect arising due to enucleation following trauma except some amount of dystopia in a 26 years old male by dermis fat grafting which gave the patient cosmetic satisfaction. Even though the surgery was performed as per the usual recommended technique it was a novel surgery for us as it was performed in a rural setup with limited resources and minimal expertise support. Keywords : Anophthalmic socket, contracted socket, orbital prosthesis, orbital reconstruction, dermis fat grafting